• Join over 1.2 million students every month
  • Accelerate your learning by 29%
  • Unlimited access from just £6.99 per month
Page
  1. 1
    1
  2. 2
    2
  3. 3
    3
  4. 4
    4
  5. 5
    5
  6. 6
    6
  7. 7
    7
  8. 8
    8
  9. 9
    9
  10. 10
    10
  11. 11
    11
  12. 12
    12
  13. 13
    13
  14. 14
    14
  15. 15
    15
  16. 16
    16
  17. 17
    17
  18. 18
    18
  19. 19
    19
  20. 20
    20
  21. 21
    21
  22. 22
    22
  23. 23
    23
  24. 24
    24
  25. 25
    25
  26. 26
    26
  27. 27
    27
  28. 28
    28
  29. 29
    29
  30. 30
    30
  31. 31
    31
  32. 32
    32
  • Level: GCSE
  • Subject: Maths
  • Word count: 3708

Maths Coursework: Number Stairs

Extracts from this document...

Introduction

Task Statement:

I have been set the task of working out the relationship between a 3 – step stair total and the position of the stair shape on the prearranged grid and other stair totals.

Aim:

As I work through this task I hope to find a formula that will help me to work out any stair total on a 10 by 10 grid.

Method:

I began by calculating the stair in a vertical sequence ranging from 1 step stair to 8 step stairs. The results of these calculations highlighted a definite pattern. These results were then summarised in a table from which a general formula was found.

Key:

= Base Number

n = Base number        

1 Step Stair:

Difference =   +1                         +1                             +1

+1                                    +1                        +1

As we can see, the stair total for a 1-step stair using 1 as the base number on a 10 by 10-number grid is 1 as the total = 1. I can therefore conclude that the general equation for a 1-step stair on a 10 by 10 number grid is 1n + 0 = stair total where n is the base number. (Shaded box).

Total of step containing 1 as its base number – Difference

= 1- 1

= 0        

(B) Base number

Total number inside

1

1

2

2

3

3

4

4

5

5

6

6

7

7

8

8

Formulae: 1n + 0 = Total

Testing the formula:

Total = 1n + 0

Total = 1 * 2 + 0

Total = 2 + 0

Total = 2

2 Step Stairs:

 Difference = +3                          +3                                 +3  

+3                              +3                                 +3  

(B) Base number

Total number inside

1

14

2

17

3

20

4

23

5

26

6

29

7

32

8

35

As we can see, the stair total for a 2-step stair using 1 as the base number on a 10 by 10-number grid is 14 as 1 + 2 + 11 = 14. I can therefore conclude that the general equation for a 2-step stair on a 10 by 10 number grid is 3n + 11 = stair total where n is the base number. (Shaded box).

Total of step containing 1 as its base number – Difference

= 14 – 3

= 11

...read more.

Middle

Total = 36n + 924

Total = 36 * 2 + 924

Total = 72 + 924

Total = 996

Formulas:

Number of steps

Total number inside (‘n’ = base number)

1

Total = 1n + 0

2

Total = 3n + 11

3

Total = 6n + 44  

4

Total = 10n + 110  

5

Total = 15n + 220  

6

Total = 21n + 385  

7

Total = 28n + 616  

8

Total = 36n + 924

Final Formula:

Section 1:

              = First Difference

              = Second Difference

Position

Term

0

0

1

1

2

3

3

6

4

10

5

15

6

21

7

28

8

36

The data above is summarised in the table below.

n

0

1

2

3

4

5

6

7

8

nth term

0

1

3

6

10

15

21

28

36

1st difference

1

2

3

4

5

6

7

8

2nd difference

1

1

1

1

1

1

1

Observation:

The differences between the nth terms were increasing which meant that I had to use quadratic sequences. The general term of a quadratic sequence is:

un =AN 2 + BN + C

a= the second difference in the sequence over 2.

b = is the coefficient of the term in n 2.

c = is the numerical value or constant value.

a = 2nd difference / 2

a = 1 / 2

Counting back, the zeros term is 0. So when n = 0, un = 0. When ‘n’ = 0, both ‘n 2’ and ‘bn’ are equal to 0 so ‘c’ = 0.

C = 0

To find the value of ‘b’, we look at the first term. When ‘n’ = 1, the value of u is 2.

un = n + bn

      = 1 + b

  2 = 1 + b

   b = 1 / 2

1/2s2+ 1/2 s

Section 2:

  = First Difference

  = Second Difference

  = Third Difference

Position

Value

0

0

1

0

2

11

3

44

4

110

5

220

6

385

7

616

8

924

 The data above is summarized in the table below.

n

0

1

2

3

4

5

6

7

8

nth term

0

0

11

44

110

220

385

616

924

1st difference

0

11

33

66

110

165

231

308

2nd difference

11

22

33

44

55

66

77

3rd difference

11

11

11

11

11

11

Nth term =an 3 + bn 2 + cn + d

When n = 1     13a+12b+1c+d=6                      Equation 1:  a + b + c + d = 0

When n = 2     23a+22b+2c+d=20                    Equation 2:  8a + 4b + 2c + d = 11

When n = 3     33a+32b+3c+d=52                    Equation 3:  27a + 9b + 3c + d = 44

When n = 4     43a+42b+4c+d=108                  Equation 4:  64a + 16b + 4c + d = 110

Subtracting equation 1 from each of the other 3 gives: 

Equation 5           7a+3b+c=11

  Equation 6           26a+8b+2c=44

  Equation 7           63a+15b+3c=110

Subtracting 2 times equations 5 from equation 6 gives:             

...read more.

Conclusion

an3 + bn2 + cn + d:

If n = 1 , 2 , 3 , 4 , 5

a+b+c+d , 8a+4b+2c+d , 27a+9b+3c+d , 64a+164+4c+d , 125a+25b+5c+d , 7a+3b+c , 9a+5b+c , 37a+7b+c , 61a+9b+c, 12a+2b , 18a+2b , 24a+2b  

6a , 6a

I am now going to match the numbers in the cubic sequence formula above to the numbers that correspond to their positions in the co-efficient in front of g sequence. 6a =

a = 1/6

12a+2b = 3

12(1/6) + 2b = 3

2 + 2b = 3

2b = 1

b = 0.5

7a+3b+c= 3

7(1/6)+3(1/2)+c = 3

c= 1/3

a+ b + c + d = 1

1/6 + ½ + 21/3 + d = 1.

d = 0

Therefore the equation for this part of the sequence will be :

(1/6 n3 + 1/2n2 + 1/3n) = coefficient of g

Section 3: The Sequence For The Constant

The sequence for the constant will go exactly the same as the sequence for the co-efficient of g as all these values are the same. Therefore the equation for this part of the sequence will be :

(1/6 n3 + 1/2n2 + 1/3n) = the constant

Conclusion

Now that we have finished the three parts of the sequence we can put them together in order to make one equation for any size step-stair on any size grid.

(1/2 n2 + 3/2n + 1) x + (1/6 n3 + 1/2n2 + 1/3 n) g + (1/6 n3 + 1/2n2 + 1/3 n) = stair total

x means the number of squares in the stair shape..

g stands for grid size.

n is the equation number. (If you don't know the equation number it is the same number as the number of squares in the 2nd column from the left of the stair shape).

Reference:

  • Internet: www.y-maths.co.uk/index.htm
  • Higher GCSE for Edexcel
  • Edexcel GCSE Mathematics higher course
  • GCSE Mathematics Revision Guide Higher Level

...read more.

This student written piece of work is one of many that can be found in our GCSE Number Stairs, Grids and Sequences section.

Found what you're looking for?

  • Start learning 29% faster today
  • 150,000+ documents available
  • Just £6.99 a month

Not the one? Search for your essay title...
  • Join over 1.2 million students every month
  • Accelerate your learning by 29%
  • Unlimited access from just £6.99 per month

See related essaysSee related essays

Related GCSE Number Stairs, Grids and Sequences essays

  1. Marked by a teacher

    Number Grid Aim: The aim of this investigation is to formulate an algebraic equation ...

    3 star(s)

    an 8 x8 grid, The first top left hand box is shown as 'n' and the size of the grid is still 'g'. The top right hand corner of the box is 2 more than the top left hand corner, so this is n+ 2.

  2. Number stairs

    constant number of [4] is consistent every time the grid size increases by [1] For any 3-step numbered grid box as shown in my table above or in the testing examples I am going to do below, and [x] as the value from the bottom left hand square and the

  1. GCSE Maths Sequences Coursework

    the sequence so; Nth term for Perimeter = 12N+6 Shaded Stage (N) 1 2 3 4 Sequence 6 12 18 24 1st difference +6 +6 +6 2nd difference I can see a clear pattern here, the sequence for shaded is going up regularly in 6's, and therefore this sequence is a linear sequence and has an Nth term.

  2. Number Grid Coursework

    Generalisation Using this apparent relationship, it can be assumed that, when a 2x2 box is placed anywhere on the grid, the difference of the two products will be z for all possible widths. Therefore, the following equation should be satisfied with any real value of a and any real

  1. Investigation of diagonal difference.

    than the length of the grid it can either be equal to the length of the grid or smaller than the length of the grid.i.e. G ? X Investigating diagonal difference of rectangular cutouts Now that I have proved my formula works for square cutouts on square and rectangular grids,

  2. Number Grids Investigation Coursework

    p2mw - pa - p2wn + p2w - a2 - apnw + apw - [apm + ap) = - p2mw + p2wnm - p2wn + p2w = w (p2 - p2m - p2mn - p2n) = wp2 (1 + mn - m - n)

  1. Algebra Investigation - Grid Square and Cube Relationships

    This will remain constant. w: The width of the cube in question. h: The height of the cube in question. d: The depth of the cube in question. g: The overall gridsize contained in the cube. s: The increment (step)

  2. Maths - number grid

    4 90 10 x 9 10 x 3 5 x 5 160 10 x 16 10 x 4 6 x 6 250 10 x 25 10 x 5 7 x 7 360 10 x 36 10 x 6 8 x 8 490 10 x 49 10 x 7 9 x

  • Over 160,000 pieces
    of student written work
  • Annotated by
    experienced teachers
  • Ideas and feedback to
    improve your own work